Konseling Individual Menggunakan Teknik WDEP untuk Meningkatkan Keterampilan Belajar Siswa - Rasdiany, Apriana Nofriastuti; Karneli, Yeni (Universitas Negeri Padang, 2021)
Learning skills are very important in learning, because with learning skills students can learn well and get maximum results. Learning skills as an asset in improving the quality of student learning. This study uses an action research method to provide an overview of the solution to the problem of low student learning skills in vocational high schools. Students are able to improve their learning skills through the technique WDEP System. This technique of WDEP improving can raise awareness of the important learning skills by conducting self-evaluations by exploring and assessing student behaviors, especially irresponsible behavior that results in low learning skills. After knowing and assessing their behavior, students together with the supervising teacher make plans for more responsible future behavior, in which there is a commitment between the supervising teacher and students. With this commitment, students are required to be responsible for the plans they have made. This will certainly help students improve their learning skills by emphasizing their responsibilities as students.